Taking Youth Suicide Seriously: Disclosure of Information between School, Family and Health Professionals in New Zealand - Stewart, James G (Victoria University of Wellington Law Review, 2001)
This paper investigates the law’s impact on disclosures of information between family, school and health professional in curbing the tragedy of youth suicide in New Zealand. The application of general privacy and confidentiality law is considered within the context of the recommended best practice espoused by the state lead New Zealand Youth Suicide Prevention Strategy. The paper concludes that the complexity and at times incoherence of current law has failed to define standards upon which disclosure decisions could be based. As such, the legal obligations of privacy and confidentiality have not been adequately married with the need for cohesion between family, school and health professional or indeed, with the best interests of the suicidal adolescent. Instead the article suggests a separate privacy and confidentiality regime that addresses the particular challenges faced by parties dealing with suicidal young people. The suggestions are based on information obtained from a national survey of secondary school principals in New Zealand.